Polare : a magazine for people with gender issues. (Petersham : The Gender Centre, 1998)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks
Redactie: PO Box 299, Petersham NSW 2049 Australia
Engels
Periodiek